Particularism and the Politics of Nature - Peruniak, Blair (My University, 2009)
This thesis is an attempt to offer an account of the practical ethics of Bruno Latour's political ecology based on Jonathan Dancy's recent work on ethical particularism with the aim of demonstrating the possibility of their entering into a fruitful alliance. I argue that Dancy's particularism offers Latour a defensible (though not uncontroversial) position through which to anticipate, and respond to, various concerns arising from the latter's attempts to minimize the role of principles in ecological-moral deliberation . In return, Latour's ecology encourages us to consider the possibility of a particularist ecological ethic while allowing us to see what is most important about particularism in the context of press ing matters of public concern.
Keywords: Philosophy; Philosophy